Upaya Penegakan Hukum terhadap Tindak Pidana Keimigrasian - Bambang Hartono (Universitas Bandar Lampung (UBL), 2012)
Relation Bilateral and also multilateral between Indonesia with the other;dissimilar state cause the current go out entry of foreigner become to mount the. Consequence from that human being movement is to the number of happened by the that good immigration collision is administrative collision and also Doing An Injustice of Immigration like existence of abuse of immigration permit, passport forgery, visa forgery and others by international syndicate organized and also oknum-oknum foreigner alone, others they conduct the doing an injustice narcotic, prostitution and terrorism,. Strive the straightening of law passing immigration action, not yet full executed. Where straightening of law of doing an injustice of immigration only limited to action imposition which is in the form of administrative do not reaching process criminal justice.